Clinical characteristics of 225 patients with COVID-19 in a tertiary Hospital near Wuhan, China - Li, Ruoqing; Tian, Jigang; Yang, Fang; Lv, Lei; Yu, Jie; Sun, Guangyan; Ma, Yu; Yang, Xiaojuan; Ding, Jianqiang (Journal of clinical virology, 2020)
[Display omitted] •The clinical characteristics of COVID-19 in a hospital near Wuhan, China have been collected.•SARS-CoV-2 is a new coronavirus that causes human disease.•Fever and cough are the common clinical manifestations.•The mortality rate was 0.89 %. The 2019 coronavirus disease (COVID-19) was first identified in Wuhan, Hubei, China in December 2019, caused by a novel coronavirus (SARS-CoV-2). There is a need to study the clinical features of patients in a hospital near Wuhan. To identify clinical features of patients with COVID-19 in a tertiary hospital near Wuhan. General information, clinical manifestations, laboratory data, and computed tomography (CT) data were collected for 225 patients diagnosed of COVID-19 admitted between January 20 and February 14, 2020, to the Hanchuan City People’s Hospital. The patients included 120 male and 105 females who had no connection to the Wuhan Huanan Seafood Market. Their average age was 50 ± 14 years. The major clinical symptoms were fever (84.44% of patients), cough (56.44% of patients), and dyspnea (4.00% of patients); 3.56%–22.67% of subjects suffered from expectoration, fatigue, chills, headache, chest pain, and pharyngalgia. Hypertension was present in 20.89% of patients. The counts of white blood cells (WBCs) and lymphocytes were normal or decreased in 86.67% and 99.11% of patients. CRP was increased in 86.22% of patients, PCT in 10.67%, and ESR in 90.22%. CT showed that 86.22% of patients had multiple patchy glassy shadows in both lungs, particularly in the peripheral area. Thirty-seven (16.44%) patients were diagnosed with severe COVID-19. Methylprednisolone was administered in 44.44% of cases. The mortality among the patients was 0.89%. Clinical characteristics of COVID-19 patients in the tertiary hospital near Wuhan are very similar to those found in Wuhan, but the lower mortality.